2020
DOI: 10.1097/pas.0000000000001498
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear and Temporal Bone Nonkeratinizing Squamous Cell Carcinomas With DEK-AFF2 Fusion

Abstract: Primary squamous cell carcinomas (SCCs) of the middle ear and temporal bone are rare and usually keratinizing by morphology. Nonkeratinizing, basaloid SCCs arising in this area are exceedingly rare, and, due to the anatomic proximity to the skull base, nasopharynx, and nasal sinuses, the differential diagnosis is broad. Most tumors with squamous differentiation arising in these subsites are either viral-induced (human papillomavirus/Epstein-Barr virus) or rarely may have specific molecular alterations (BRD4-NU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…A novel AFF2::RET fusion has been identified in a single case of lung adenocarcinoma, with the breakpoint occurring between intron 7 of AFF2 and exon 11 of RET , 21 with no other oncogenic drivers being present. Other recently reported fusions demonstrated AFF2 as the 3′ partner, similar to our current case, including recurrent DEK::AFF2 fusions in nonkeratinizing squamous cell carcinomas of the sinonasal tract 22–24 . Thus far fewer than 20 of these head and neck squamous cell carcinomas have been identified, being characterized by the first 7 exons of DEK fused to exons 4, 6, or 9 of AFF2 , respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A novel AFF2::RET fusion has been identified in a single case of lung adenocarcinoma, with the breakpoint occurring between intron 7 of AFF2 and exon 11 of RET , 21 with no other oncogenic drivers being present. Other recently reported fusions demonstrated AFF2 as the 3′ partner, similar to our current case, including recurrent DEK::AFF2 fusions in nonkeratinizing squamous cell carcinomas of the sinonasal tract 22–24 . Thus far fewer than 20 of these head and neck squamous cell carcinomas have been identified, being characterized by the first 7 exons of DEK fused to exons 4, 6, or 9 of AFF2 , respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Other recently reported fusions demonstrated AFF2 as the 3 0 partner, similar to our current case, including recurrent DEK::AFF2 fusions in nonkeratinizing squamous cell carcinomas of the sinonasal tract. [22][23][24] Thus far fewer than 20 of these head and neck squamous cell carcinomas have been identified, being characterized by the first 7 exons of DEK fused to exons 4, 6, or 9 of AFF2, respectively. Finally, a Japanese study reported a STAG2::AFF2 fusion in a single case of pediatric EBV-negative peripheral T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…36 The AFF2 gene encodes a putative transcriptional activator that is a member of the AF4/FMR2 gene family and fusion genes involving this gene, such as KMT2A-AFF2 and DEK protooncogene (DEK)-AFF2, were identified in acute leukaemia and squamous cell carcinoma respectively. 37,38 ITPR2-FSTL4 was also identified as a novel fusion transcript in PTCL. The predicted protein from the ITPR2-FSTL4 fusion gene lacks most of the functional domains included in ITPR2.…”
Section: Discussionmentioning
confidence: 96%
“…STAG2, encoding a subunit of the cohesin complex, regulating the separation of sister chromatids during cell division and playing a major role in transcription regulation that is associated with specific promoter chromatin architecture, is a frequent target of mutational inactivation in various tumour types 35 and STAG2 knockdown caused an increase in haematopoietic stem cell‐specific genes in primary human CD34 + cells 36 . The AFF2 gene encodes a putative transcriptional activator that is a member of the AF4/FMR2 gene family and fusion genes involving this gene, such as KMT2A‐AFF2 and DEK proto‐oncogene ( DEK ) ‐AFF2 , were identified in acute leukaemia and squamous cell carcinoma respectively 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…This study was quickly followed by additional reports of SCCs with DEK::AFF2 fusions arising from the mucosa of the sinonasal tract and middle ear. [20][21][22] In 2021, collaborative work including one of the authors of this editorial reported a series of 7 cases of DEK::AFF2 SNSCC, which, unlike many of the earlier cases, display bland morphology. 23 This case series included several patients previously described in publications by our group as so-called "low-grade papillary Schneiderian carcinoma," which are polypoid, bland squamous neoplasms mimicking sinonasal papillomas but which have been found to recur and occasionally metastasize.…”
Section: Gene Fusion Snsccmentioning
confidence: 99%